Pelaksanaan Sanksi Pidana Terhadap Anak Korban Penyalahguna Narkotika (Studi Kasus LPKA Kelas I Medan) - Shafira Utami; Zulkarnain Zulkarnain (JURNAL HUKUM PELITA, 2025)
This research aims to understand the application of legal sanctions for child victims of narcotics abusers from the perspective of Islamic criminal law as well as the challenges and solutions in implementing legal sanctions for child victims of narcotics abusers. This research uses a qualitative method with this type of research being empirical juridical or field research which is usually called (field research) case study at LPKA Class I Medan. Data collection techniques include interviews, data obtained in the field which describes, describes, matches and compares to draw conclusions. The interview was aimed at child victims of narcotics abuse. Data collection tools in this research are observation, interviews and documentation. From these results it can be concluded that the teachings of Islamic Criminal Law provide punishment for crimes against minors which are carried out in accordance with the provisions of the Al-Qur'an and Hadith with consideration of the child's psychology so that if they cause material loss then the parents who are punished will pay compensation. Thus, this research produces a general conclusion that Islamic Criminal Law needs to be perfected by adopting the provisions of Islamic Criminal Law in order to protect and guarantee the rights of children and their future